2015
DOI: 10.1371/journal.pone.0138227
|View full text |Cite
|
Sign up to set email alerts
|

Did Socioeconomic Inequality in Self-Reported Health in Chile Fall after the Equity-Based Healthcare Reform of 2005? A Concentration Index Decomposition Analysis

Abstract: ObjectiveChile, a South American country recently defined as a high-income nation, carried out a major healthcare system reform from 2005 onwards that aimed at reducing socioeconomic inequality in health. This study aimed to estimate income-related inequality in self-reported health status (SRHS) in 2000 and 2013, before and after the reform, for the entire adult Chilean population.MethodsUsing data on equivalized household income and adult SRHS from the 2000 and 2013 CASEN surveys (independent samples of 101 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 47 publications
1
26
0
1
Order By: Relevance
“…where c is the concentration index, y i is the health sector variable of individual i, R i is the fractional ranks of income, and µ is the mean of y i . The health concentration index can be decomposed into the contributions of each determinant to observed income-related health inequality-in which, each contribution is the product of the sensitivity of health with respect to that determinant and the degree of income-related inequality in that determinant [28]. Health economists normally put forward the different decomposition methods in the literature to decompose the concentration index.…”
Section: Discussionmentioning
confidence: 99%
“…where c is the concentration index, y i is the health sector variable of individual i, R i is the fractional ranks of income, and µ is the mean of y i . The health concentration index can be decomposed into the contributions of each determinant to observed income-related health inequality-in which, each contribution is the product of the sensitivity of health with respect to that determinant and the degree of income-related inequality in that determinant [28]. Health economists normally put forward the different decomposition methods in the literature to decompose the concentration index.…”
Section: Discussionmentioning
confidence: 99%
“…This may have been due to other health sector-related reforms introduced before the TSL implementation, as well as the lack of proper implementation of the TSL and insufficient funds paid to the health system [ 18 ]. Another study reported that equity-based healthcare reform significantly reduced income-related inequality [ 38 ]. Moreover, studies have shown positive effects of economic or health system reforms on equity in healthcare financing [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration index is between -1 and 1. A positive number indicates that the health variable is distributed toward the rich [ 21 ]. In the analysis, the health variable of interest is the occurrence of CHE.…”
Section: Methodsmentioning
confidence: 99%